Carnitine and Depression - Liu, Ting; Deng, Kunhong; Xue, Ying; Yang, Rui; Yang, Rong; Gong, Zhicheng; Tang, Mimi (Frontiers in Nutrition, 2022)
Depression has become one of the most common mental diseases in the world, but the understanding of its pathogenesis, diagnosis and treatments remains insufficient. Carnitine is a natural substance that exists in organisms, which can be synthesized in vivo or supplemented by intake. Relationships of carnitine with depression, bipolar disorder and other mental diseases have been reported in different studies. Several studies showed that the level of acylcarnitines (ACs) changes significantly in patients with depression compared with healthy controls while the supplementation of acetyl-L-carnitine is beneficial to the treatment of depression. In this review, we aimed to clarify the effects of ACs in depressive or bipolar patients and to explore whether ACs might be the biomarkers for the diagnosis of depression and provide new ideas to treat depression.